Peculiarities in training pilots for civil aviation of Ukraine - Коростелев, А. Е.; Янин, В. Д. (Proceedings of National Aviation University (archive), 1999)
Documents issued to aviation specialists of Ukraine should correspond to international standards. Described are the peculiarities in training commercial and transport pilots